Early Intervention Referral Rates of Infants With Neonatal Opioid Withdrawal Syndrome Are Not Significantly Affected by Race, Payor, Maternal Medication for Opioid Use Disorder, or NICU Hospitalization - Weijen W. Chang; Laura Lee; S. Roberge; M. S. Chang; Elizabeth Peacock‐Chambers (2025)
In this study, we examined the factors influencing enrollment in early intervention (EI) programs for neonates diagnosed with nonopioid-associated neonatal abstinence syndrome (NAS) and neonatal opioid withdrawal syndrome (NOWS). The primary goal was to examine characteristics linked to completing an individualized family service plan (IFSP), marking EI enrollment. Patient records were reviewed using data from neonates discharged with NOWS/NAS at a Massachusetts hospital in 2017 to identify demographic and medical factors related to NOWS/NAS cases. Out of 125 cases, 111 were analyzed, with patient outcomes analyzed in subgroups of those with NOWS and non-opioid-associated NAS. Findings indicated that neonates with NICU hospitalization, race, payor, and maternal medication for opioid use disorder (MOUD) did not have significantly different rates of IFSP completion. Additionally, no significant difference was observed in IFSP completion rates between neonates with NAS or NOWS. This study reports baseline data from a quality improvement initiative not designed to detect statistically significant differences. However, it highlights potential areas for further investigation to improve EI access for NOWS- and NAS-affected neonates, although more extensive studies are needed to further elucidate these differences.